رؤية استشرافية للقطاع الزراعي الجزائري على ضوء استراتيجية التجديد الفلاحي و الريفي الجديدة للفترة 2015-2019 - علة, مراد (جامعة الوادي- University of Eloued, 2017)
The Agricultural development occupies an important place in the priorities of economic policies and investment in many programs of economic development and reform in the Arab countries, given the importance of agriculture as a source of food and raw materials; as a sector that absorbs a high percentage of the labor force. Which depends on the economy of oil resources, whose prices are deteriorating continuously; and the negative effects on the economy, which called for giving more importance to the agricultural sector in Algeria, where a practical plan was designed to improve the profitability of the agricultural sector within the strategic Economic diversification.
مقال
Keywords: للقطاع الزراعي ،الجزائري ، استراتيجية التجديد الفلاحي و الريفي; agricultural sector Economic diversification.